Prácticas verdes y su influencia en el comportamiento de compra del consumidor de restaurantes de comida buffet - Andrade Lucas, Cristhian Enrique (2025)
The objective of this study was to evaluate green practices and their influence on consumer purchasing behavior in buffet-style restaurants in Manta city. A mixed-methods approach was used, combining bibliographic and field research. Analytical, descriptive, and correlational methods were applied to analyze the relationship between sustainable practices in restaurants and consumer behavior. Surveys were used as the primary data collection technique. The results revealed a clear consumer preference for restaurants that adopt eco-friendly practices, with a majority willing to choose establishments committed to environmental responsibility. A moderate positive correlation was found (ρ = 0.685), supporting the relationship between green practices and consumer behavior. However, a gap between intention and actual behavior was also identified, which represents the main challenge for sustainable restaurants. This suggests the need for strategies that effectively communicate the added value of green practices, particularly regarding pricing. Therefore, it is concluded that strategies must be implemented both internally—through improvements in restaurant structure and operations—and externally, by strengthening marketing strategies to highlight the added value of existing green practices.